The Development of Theory and Application of Newton's Law: A Systematic Literature Review - Fatkhurrohman, Mukhammad Aji; Hamidah, Ida; Samsudin, Achmad; Suhandi, Andi (KnE Social Sciences, 2024)
This study aims to identify research trends in the development of theories and research applications of Newton’s law from 2017 to 2023. The method used is a systematic literature review SLR using the PRISMA Framework, which includes four steps: identification, screening, eligibility, and inclusion. The keyword used for the search is “Newton Law”, and the article search is done in the databases Scopus, Springer, Emerald, and IEEE. From the search results, 26,494 articles were obtained, Through the screening, eligibility, and inclusion process, 13 articles met the criteria. The results and discussion show that Newton’s Law theory still plays a key role in understanding physics. The scientific debate remains relevant, and applications of Newton’s Law can be found in fluid physics, quantum physics, cosmology, and mathematics. Keywords: application, newton’s laws, systematic literature review, theory